Sonodynamic Cancer Therapy by Mn(I)-tricarbonyl Complexes via Ultrasound-triggered CO Release and ROS Generation - Kumar Yadav A.; Singh V.; Acharjee S.; Saha S.; Kushwaha R.; Dutta A.; Koch B.; Banerjee S. (My University, 2025)
A novel ferrocene conjugated Mn(I)-tricarbonyl complex viz [Mn(Fc-tpy)(CO)3Br] (Mn2) where, Fc-tpy=4′-ferrocenyl-2,2′:6′,2′′-terpyridine was synthesized and fully characterized along with its non-ferrocene analog [Mn(Ph-tpy)(CO)3Br] Ph-tpy=4′-phenyl-2,2′:6′,2′′-terpyridine (Mn1) for ultrasound (US) activated anticancer applications. The X-ray structure of Mn2 confirmed its distorted octahedral geometry. Mn1 and Mn2, for the first time, showed US-triggered release of CO and ROS generation (1O2 and ⋅OH) in an aqueous solution from any Mn(I)-tricarbonyl complexes, indicating its potential for synergetic CO gas therapy and sonodynamic therapy. The above-mentioned in-solution chemistry was successfully translated into in vitro cellular models. These complexes showed unprecedented US-triggered toxicity against T-cell lymphoma and human breast cancer cells (IC50 for Mn2<1 μM) while were minimally toxic without US or against normal spleen and human embryonic kidney cells. Mn2 was ca. 12 fold more anticancer active than Mn1, indicating that the ferrocene conjugation augmented the US sensitivity. The apoptotic sonotoxicity of Mn2 was due to US-promoted mitochondrial depolarization via ROS generation and CO release. The apoptosis was triggered by caspase 3 activation. This is the first report of Mn(I)-tricarbonyl-based sonosensitizers for cancer SDT. Overall, this study, for the first time, establishes the effectiveness of 3d metal carbonyls in SDT. © 2024 Wiley-VCH GmbH.